P1189OFFICE AND AMBULATORY RECORDING OF CENTRAL AORTIC PRESSURES, WAVE REFLECTION AND ARTERIAL STIFFNESS INDICES IN PERITONEAL DIALYSIS PATIENTS. (6th June 2020) - Vaios, Vasilios; Georgianos, Panagiotis; Vareta, Georgia; Geropoulou, Evaggelia; Ntounousi, Evangelia; Papagianni, Aikaterini; Zebekakis, Pantelis; Liakopoulos, Vassilios
Abstract: Background and Aims: Among peritoneal dialysis (PD) patients, aortic blood pressure (BP) and arterial stiffness indices are independent predictors of cardiovascular morbidity and mortality. Previous studies in PD patients recorded these parameters only in the office. The present study provides comparisons between office and ambulatory recordings of these parameters and explores the association of demographic, clinical and hemodynamic variables with high arterial stiffness. Method: In 81 stable PD patients (mean age: 61.3±16.3 years; male gender: 64.2%), brachial and aortic BP, heart rate-adjusted augmentation index (AIx75) and pulse wave velocity (PWV) were recorded after a 5-minute seated rest in the office using the oscillometric device Mobil-O-Graph (IEM, Stolberg, Germany). Subsequently, all patients underwent ambulatory recording of these parameters with the same device for 24 hours. Logistic regression analysis was performed to identify factors independently associated with high ambulatory PWV. Results: As expected, office brachial systolic BP (SBP) was higher than 24-hour brachial SBP (134.2±22.7 vs. 129.0±18.0 mmHg, P<0.01). Similarly, office aortic SBP was higher than 24-hour aortic SBP (122.5±20.1 vs. 117.1±16.1 mmHg, P=0.001). By contrast, office AIx75 did not differ from 24-hour AIx75 (23.4%±11.7% vs. 23.9%±9.3%, P=0.602), whereas office PWV was only slightly higher than 24-hour PWV (9.2±2.3 vs. 9.0±2.2m/sec, P=0.001). Participants stratified in the high PWV tertile were older, had higher 24-hour mean BP (MBP) and had more commonly history of diabetes, dyslipidemia and coronary heart disease. In multivariate analysis, older age (OR: 4.23; 95% CI: 1.59-11.24) and higher 24-hour MBP (OR: 1.31; 95% CI: 1.03-1.67) were the only independent determinants of high PWV. Conclusion: Among patients on PD, brachial and central aortic pressures recorded in the office were higher than 24-hour ambulatory pressures, whereas this variation between office and ambulatory recordings was diminished for AIx75 and PWV. Future studies are warranted to explore the prognostic significance of these parameters in the PD population.